ICI-induced cardiovascular toxicity: mechanisms and immune reprogramming therapeutic strategies - Zheng, Jixuan; Yi, Yanyu; Tian, Tingchen; Luo, Shunming; Liang, Xiao; Bai, Yu (Frontiers in Immunology, 2025)
The advent of immune checkpoint inhibitors (ICIs) has revolutionized cancer treatment, offering life-saving benefits to tumor patients. However, the utilize of ICI agents is often accompanied by immune-related adverse events (irAEs), among which cardiovascular toxicities have attracted more and more attention. ICI induced cardiovascular toxicities predominantly present as acute myocarditis and chronic atherosclerosis, both of which are driven by excessive immune activation. Reprogramming of T cells and macrophages has been demonstrated as a pivotal factor in the pathogenesis of these complications. Therapeutic strategies targeting glycolysis, fatty acid oxidation, reactive oxygen species (ROS) production and some other key signaling have shown promise in mitigating immune hyperactivation and inflammation. In this review, we explored the intricate mechanisms underlying ICI-induced cardiovascular toxicities and highlighted the protective potential of immune reprogramming. We emphasize the roles of T cell and macrophage reprogramming in the heart and vasculature, showcasing their contributions to both short-term and long-term regulation of cardiovascular health. Ultimately, a deeper understanding of these processes will not only enhance the safety of ICIs but also pave the way for innovative strategies to manage immune-related toxicities in cancers therapy.